2016
DOI: 10.1016/j.bbrc.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic regulation of HIF-1α by SIRT1 in MPP + treated SH-SY5Y cells

Abstract: Both silent information regulator 1 (SIRT1) and hypoxia inducible factor 1 (HIF-1) have been found to play important roles in the pathophysiology of Parkinson’s disease (PD). However, their mechanisms and their relationship still require further study. In the present study, we focused on the change and relationship of SIRT1 and HIF-1α in PD. PD cell models were established by using methyl-4-phenylpyridinium (MPP+), which induced inhibition of cell proliferation, cell cycle arrest and apoptosis. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
(30 reference statements)
5
23
0
Order By: Relevance
“…Recently, the neuroprotective properties of SIRT1 have also been described in PD depending on anti‐apoptotic and anti‐oxidant features (Tsai et al, ; Zou et al, ). In present study, we found that MPP + treatment obviously decreased the SIRT1 activity, SIRT1 mRNA and protein levels in SH‐SY5Y cells, which is also consistent with the research done by Dong et al (), Tao et al (), and Zou et al (). Remarkably, some researchers reveal that SIRT1 contributes to the protective effects of salidroside against kainic acid‐induced status epilepticus (Si et al, ), d ‐galactose‐induced rat model of Alzheimer's disease (AD) (Gao et al, ), and hypoxia‐induced neurodegeneration (Barhwal et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recently, the neuroprotective properties of SIRT1 have also been described in PD depending on anti‐apoptotic and anti‐oxidant features (Tsai et al, ; Zou et al, ). In present study, we found that MPP + treatment obviously decreased the SIRT1 activity, SIRT1 mRNA and protein levels in SH‐SY5Y cells, which is also consistent with the research done by Dong et al (), Tao et al (), and Zou et al (). Remarkably, some researchers reveal that SIRT1 contributes to the protective effects of salidroside against kainic acid‐induced status epilepticus (Si et al, ), d ‐galactose‐induced rat model of Alzheimer's disease (AD) (Gao et al, ), and hypoxia‐induced neurodegeneration (Barhwal et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Its beneficial effects are widely explored in neurodegenerative diseases, including PD (Ramadori et al, 2008). Numerous studies have revealed that SIRT1 level in dopaminergic neurons is obviously down-regulated in toxic models of PD (Pallas et al, 2008;Albani et al, 2009;Donmez and Outeiro, 2013), and SIRT1 overexpression or activation attenuates neuronal death as well as neurodegeneration in both vivo and vitro PD models (Albani et al, 2009;Dong et al, 2016). Notably, previous studies suggested that multiple signaling pathways including phosphoinositide 3-kinase (PI3K), MAPKs, and other pathways are associated with the neuroprotection of SIRT1 (Zhang et al, 2016b;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Here, mRNA level of Sirt1 was found (Figure 5a). Consistently, the level of Sirt1 is markedly downregulated in toxic models of PD (Dong et al, 2016;Pallas et al, 2008). In contrast, levels of SIRT1 increase as a protective response to neurodegenerative conditions in some models of neurodegeneration (Kim et al, 2007).…”
Section: Discussionmentioning
confidence: 71%
“…Two research groups have described morphological and gene expression changes in this cell line in stiff environments [53,54]. It is possible that ALK-mutated cells respond to ECM changes through epigenetic alterations or genetic mutations undetected by the techniques we employed [53,[75][76][77].…”
Section: Discussionmentioning
confidence: 99%